2005
DOI: 10.1021/es048771g
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic CYP1A Induction by Dioxin-like Compounds, and Congener-Specific Metabolism and Sequestration in Wild Common Cormorants from Lake Biwa, Japan

Abstract: The present study examines the effects of polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and coplanar polychlorinated biphenyls (Co-PCBs) on hepatic cytochromes P450 (CYP) in the wild population of common cormorants from Lake Biwa, Japan, and discusses functional roles of CYP1A in terms of correlation analysis between tissue concentrations of individual congeners and expression levels of CYP1A. Levels of alkoxyresorufin (methoxy-, ethoxy-, pentoxy-, and benzyloxyresorufin) O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
52
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 55 publications
10
52
1
Order By: Relevance
“…The concentration ratios of certain congeners (congener x/PCB169) had negative correlations with CYP1A-like protein content, possibly as a result of preferential metabolism, as reported for some other species [14,15,40]. In pigs, the concentration ratio of PCB114 showed a significant negative correlation with CYP1A-like protein levels (r ¼ À0.44, p < 0.05).…”
Section: Drcs In Pig Livers and Toxicological Significancesupporting
confidence: 62%
“…The concentration ratios of certain congeners (congener x/PCB169) had negative correlations with CYP1A-like protein content, possibly as a result of preferential metabolism, as reported for some other species [14,15,40]. In pigs, the concentration ratio of PCB114 showed a significant negative correlation with CYP1A-like protein levels (r ¼ À0.44, p < 0.05).…”
Section: Drcs In Pig Livers and Toxicological Significancesupporting
confidence: 62%
“…Field studies have reported negligible bioaccumulation of TCDF from prey items in Forster's terns and herring gulls [7,50]. This may be attributable to preferential metabolism of 2,3,7,8-TCDF, which a number of studies have reported in various avian species exposed to mixtures of AhR-active compounds [51][52][53]. Data on avian toxicokinetics from controlled laboratory studies are limited, but mammalian studies have shown the rate of metabolism of 2,3,7,8-TCDF to be elevated with increased concentrations of dioxin-like compounds and the subsequent induction of cytochrome P450 1A1 or 1A2, whereas 2,3,4,7,8-PeCDF is preferentially sequestered in the liver [54,55].…”
Section: Tissue-based Exposurementioning
confidence: 99%
“…Furthermore, we have clarified that cormorants collected from Lake Biwa in Japan accumulate high levels of DRCs in the liver and induce CYP1A4 and 1A5 at transcriptional and translational levels (Kubota et al, 2004(Kubota et al, , 2005(Kubota et al, , 2006. While extensive data are available on mammalian CYP1A1 and 1A2, enzymatic properties of CYP1A4 and 1A5 isozymes in avian species have been poorly understood until now.…”
Section: Introductionmentioning
confidence: 99%
“…Expression of recombinant CYP1A proteins in yeast microsomes was confirmed by the reduced CO-difference spectrum and detected by western blotting. Kinetics and specificity of the CYP1A enzymes toward O-dealkylation of methoxy-, ethoxy-, pentoxy-and benzyloxyresorufin (MROD, EROD, PROD and BROD, respectively) were investigated as described by Kubota et al (2005) with some modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation